Conservative management of esophageal perforation following obesity surgery - Ardengh, José Celso; Domene, Carlos Eduardo; Valiati, Loana Heuko; Morrell, Alexander Charles (São Paulo Medical Journal, 2006)
CONTEXT: Laparoscopic adjustable silicone gas- tric banding (LASGB) is one of the several surgi- cal techniques for treating patients with morbid obesity. Erosion and perforation in the gastric chamber caused by LASGB are rare complications that have already been described. There have not yet been any reports of perforation of the middle esophagus during this procedure. CASE REPORT: The authors describe the case of a patient who presented the complication of very extensive perforation of the middle third of the esophagus following LASGB. This was successfully managed using conservative treatment.